PROFIL FIJAI WARGA BELAJAR PROGRAM KESETARAAN PAKET A SANGGAR KEGIATAN BELAJAR (SKB) - Putri Mardayani; Rufran Zulkarnain; Suardi Jasma (Jurnal Pendidikan Sepanjang Hayat, 2019)
This study was aimed at describing the profile of Fijai, a student of program kesetaraan paket A Sanggar Kegiatan Belajar of Bengkulu municipality(case study on Fijai who is also a clown). This study used qualitative method. Data collection was done by interview , documentation, and observation. The subjects of this study included Fijai's parents and Fijai's tutor at program kesetaraan paket A Sanggar Kegiatan Belajar of Bengkulu municipality. Data validity was examined using triangulation of subject, technique and time. Data were analyzed through three steps which were data reduction, data presentation, and conclusion drawing. From the results, Fijai's profile was as follows. Firstly, how was Fijai's family background? His parents did not have a job except to help him work as a clown. Fijai got Rp 2,500,000/month from his job as a clown. Secondly, how was his study at program kesetaraan paket A Sanggar Kegiatan Belajar of Bengkulu municipality? He always attended the class once a week. Thirdly,how did he do his job as a clown? He started his job from 10 A.M. until 5 P.M. He moved around while doing his job, sometimes at Suka Merindu traffic light, traffic light near the roundabout, and other traffic lights. Fourthly,how was his parents' response on his education and his job as a clown? His parents agreed with his education at SKB and his job as a clown did not disturb his education. Fively,how was his tutor's response on his education and his job as a clown? According to his tutor he had highly enthusiasm in studying, he always attended the class once a week. Sixly, how was his achievement in package A program? His achievement was increasing per semester. Keywords : The profile of Fijai, student, package A equivalence program